In Vitro and In Vivo Genotoxicity of Polystyrene Microplastics: Evaluation of a Possible Synergistic Action with Bisphenol A - Alfredo Santovito; Mattia Lambertini; Alessandro Nota (Journal of Xenobiotics)
The ubiquitous presence of plastics represents a global threat for all ecosystems and human health. In this study, we evaluated, in vitro and in vivo, the genotoxic potential of different concentrations of polystyrene microplastics (PS-MPs) and their possible synergistic interactions with bisphenol-A (BPA). For the in vitro and the in vivo assays, we used human lymphocytes and hemocytes from Lymnaea stagnalis, respectively. The genomic damage was evaluated by the micronucleus assay, and differences in eggs laid and growth of L. stagnalis were also evaluated. In human lymphocytes, PS-MPs alone at the concentration of 200 μg/mL and in association with BPA 0.100 µg/mL significantly increased the frequencies of micronuclei and nuclear buds, indicating a possible in vitro genotoxic additive action of these two compounds. Vice versa, PS-MPs did not result in genotoxicity in hemocytes. Our results indicated that PS-MPs have genotoxic properties only in vitro and at a concentration of 200 µg/mL; moreover, this compound could intensify the genomic damage when tested with BPA, indicating possible cumulative effects. Finally, PS significantly reduced the growth and the number of laid eggs in L. stagnalis.